The Influence of the Government Internal Control System During the COVID-19 Pandemic on Fraud Prevention at Universitas Tadulako - Riyan Muhamad L Djalalembah; Yuliana; Syaifuddin Rizal (Universitas Muhammadiyah Palu, 2025)
Fraud can occur even within educational institutions (universities) and research organizations. Budget management in universities has become a primary concern for decision-makers at both the university and faculty levels. At the end of 2019, the world was struck by the Coronavirus Disease (COVID-19) pandemic. To control the spread of COVID-19 on campus, Universitas Tadulako implemented restrictions on campus activities, combining Work from Home (WFH) and Work from Office (WFO) arrangements within the Rectorate, Faculties, and other administrative units. Each work unit scheduled employees for on-campus activities. Teaching and examinations were conducted online, and student activities were temporarily held virtually. This study employs a survey research design, utilizing a quantitative approach with a verificative research method. The research respondents consist of leaders from each work unit who serve as budget users at Universitas Tadulako, totaling 136 work units. The findings indicate that the government’s internal control system has a significant simultaneous effect on fraud prevention at Universitas Tadulako. Specifically, the control environment significantly influences fraud prevention, risk assessment significantly impacts fraud prevention, control activities do not have a significant effect on fraud prevention, information and communication do not significantly affect fraud prevention, and monitoring has a significant impact on fraud prevention at Universitas Tadulako.